STRATEGI MAHASISWA PENGENALAN LAPANGAN PERSEKOLAHAN (PLP II) DALAM MENGELOLA PEMBELAJARAN DAN MENINGKATKAN KEAKTIFAN SIAWA DI SMAN 13 BONE - Aryanindya Yuni Alfyanti; Sri Wahyuni; Raihan Habibi; Andi sulistyawati; Nia Ramadani; Sania Mustika; Syahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the strategies employed by students participating in the School Field Introduction Program (PLP II) in managing learning activities and enhancing student engagement at SMAN 13 Bone. PLP II is a field practice program that provides education students with opportunities to directly apply their pedagogical and professional competencies in schools. This research employed a qualitative approach using a descriptive method. Data were collected through observations, interviews, and documentation during the implementation of the PLP II program. The findings revealed that PLP II students applied various instructional strategies, including group discussions, question-and-answer sessions, collaborative learning, the use of engaging learning media, and the provision of motivation and feedback to students. These strategies successfully created a more interactive learning environment, increased student participation in the learning process, and encouraged students to become more active in asking questions, expressing opinions, and collaborating with their peers. Furthermore, PLP II students encountered several challenges, such as differences in students’ characteristics and limited instructional time, which were addressed through adjustments in teaching methods and learning approaches. Therefore, the learning management strategies implemented by PLP II students contributed positively to improving student engagement at SMAN 13 Bone.